Nutritional physiology of the Santa Ana sucker (Catostomus santaanae): A threatened freshwater fish endemic to Southern California. (27th January 2020) - Nguyen‐Phuc, Bao‐Quang; Demetropoulos, Carl; Stewart, Sam; Saffarinia, Parsa; Bastian Salgado, José; Hawkins, Elin; Frederick, Alyssa R.; German, Donovan P.
Abstract: The herbivorous fish Catostomus santaanae is a federally "threatened" freshwater fish species endemic to southern California and is the centre of legal battles over water use. Because little is known about the nutritional ecology of this species, we investigated the nutritional physiology of C. santaanae to better understand their dietary and energetic needs with the goal of generating data useful in conservation efforts. Individuals of C. santaanae were raised for six weeks on an algal diet in the laboratory. They digested approximately 45%, 55% and 80% of protein, soluble carbohydrate and lipid, respectively, from the algal diet. Their metabolic rate ( 0.0024 mg O2 min −1 g −1 ) suggested they would need to eat more than their body mass per day of an algal diet to thrive. Digestive enzyme activities of the laboratory‐reared and wild‐caught fish showed patterns typical of a "plug‐flow reactor" gut with high intake and rapid gut transit. However, lipase activities remained elevated throughout the gut, and this result, coupled with the lipid digestibility data, and evidence of feeding selectivity on specific diatom taxa in nature, suggests that C. santaanae targets diatoms as it grazes and that diatom lipid may be crucial to their survival. Our data set provides parameters that can be used in conservation modelling efforts towards habitat restoration.